2017
DOI: 10.1177/0272431617725196
|View full text |Cite
|
Sign up to set email alerts
|

South African Adolescents’ Neighborhood Perceptions Predict Longitudinal Change in Youth and Family Functioning

Abstract: This study examined South African early adolescent youth (aged 10 to 14) and their female caregivers (N = 99 dyads) participating in an HIV prevention intervention over a period of eight months. We examined youth perceptions of neighborhood cohesion, safety, and collective monitoring as they related to concurrent and longitudinal associations with youth (externalizing behavior and hope about the future) and family (parent-youth relationship quality, parental involvement, and parental responsiveness to sex comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In Italy, for example, children attending middle school (but not primary school) may move to and from school without being accompanied, upon written parental consent. Because experiences in and perceptions of their community may shape developmental outcomes of youth (e.g., Brody et al, 2001; Cook, Herman, Phillips, & Settersten, 2002; Lenzi et al, 2012; Tarantino et al, 2017; Vieno, Nation, Perkins, Pastore, & Santinello, 2010; Witherspoon & Hughes, 2013), it is important for researchers to dispose of tools that allow a reliable and valid assessment of SOC in this developmental period.…”
Section: Soc Among Early Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Italy, for example, children attending middle school (but not primary school) may move to and from school without being accompanied, upon written parental consent. Because experiences in and perceptions of their community may shape developmental outcomes of youth (e.g., Brody et al, 2001; Cook, Herman, Phillips, & Settersten, 2002; Lenzi et al, 2012; Tarantino et al, 2017; Vieno, Nation, Perkins, Pastore, & Santinello, 2010; Witherspoon & Hughes, 2013), it is important for researchers to dispose of tools that allow a reliable and valid assessment of SOC in this developmental period.…”
Section: Soc Among Early Adolescentsmentioning
confidence: 99%
“…A handful of studies investigating SOC has also been conducted among early adolescents, that is, in the age span between 10 and 14 years (e.g., Chipuer, Bramston, & Grace, 2003; DiClemente et al, 2016; Giardiello, 2016; Seider, Novick, & Gomez, 2013; Tarantino et al, 2017; Vieno et al, 2007). However, such works relied on measures developed for adults or ad hoc scales to assess SOC among early adolescents.…”
Section: Measuring Soc Among Early Adolescentsmentioning
confidence: 99%
“…In the literature, there are few studies investigating sense of community (SOC) among early adolescents, that is, in the age span between 10 and 14 years (e.g., Chipuer, Bramston, & Grace, 2003; DiClemente et al, 2016; Giardiello, 2016; Seider, Novick, & Gomez, 2013; Tarantino et al, 2017; Vieno, Santinello, Pastore, & Perkins, 2007). Early adolescence is characterised by dramatic changes at both the biological (e.g., puberty) and the social level (e.g., the transition from primary to middle schools in most educational systems), which may make this period especially challenging (Eccles, 1999; Eccles & Roeser, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing experience of autonomous mobility facilitates, in turn, the formation of social bonds with peers and adults in their neighbourhood and an increasing social understanding of the world outside (Chawla, 1992; Eccles et al, 1991; Pacilli et al, 2013; Prezza & Pacilli, 2007) and, ultimately, form their own neighbourhood experience (Brody et al, 2001; Burton, Price‐Spratlen, & Spencer, 1997). Such experiences constitute a crucial factor for the consolidation of SOC (e.g., Chipuer et al, 2003; DiClemente et al, 2016; Giardiello, 2016; Seider et al, 2013; Tarantino et al, 2017; Vieno et al, 2007). SOC has been defined as “a feeling that members have of belonging, a feeling that members matter to one another and to the group, and a shared faith that members' needs will be met through their commitment to be together” (McMillan & Chavis, 1986, p. 9).…”
Section: Introductionmentioning
confidence: 99%
“…Although previous research in high‐income settings has shown that adolescent and adult service users are likely to differ in terms of their treatment needs and on what they consider beneficial aspects of SUD treatment , it is unclear whether these findings can be extrapolated to less resourced countries like South Africa. High rates of poverty and youth unemployment, lack of recreational and educational opportunities, and communities fractured by violence characterise the context within which many young South Africans live . These structural‐contextual factors are likely to impact on adolescents' perceptions of what is needed for effective SUD treatment.…”
Section: Introductionmentioning
confidence: 99%